2019
DOI: 10.1007/s41809-019-00025-5
|View full text |Cite
|
Sign up to set email alerts
|

Predicting (variability of) context effects in language comprehension

Abstract: Predicting variability in context effects is a timely enterprise considering that psycho-and neurolinguistic research has assessed how language processing depends on the perceived context, the body, and long-term linguistic knowledge of the language user. The current evidence suggests that some context effects may be systematically more robust than others and that language user characteristics are an influential modulator of context-sensitive comprehension. Reviewing psycholinguistic evidence, I argue for cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 129 publications
(177 reference statements)
1
5
0
Order By: Relevance
“…This perspective is congruent with that proposed by Altmann and Kamide (2007), in which language processing reflects an increasingly complex mental world as the comprehender draws on their knowledge of scenes and events [see also work by McRae and Matsuki (2009)showing rapid effects of world knowledge on comprehension]. Critically, Knoeferle (2019) proposes that not all effects of visual context may be caused by the same underlying mechanism-distinct language-world relations elicit distinct context effects-and demonstrates a strong role for comprehender-specific characteristics modulating context effects during comprehension.…”
Section: Language Comprehension and Visual Context: An Integrated Persupporting
confidence: 73%
“…This perspective is congruent with that proposed by Altmann and Kamide (2007), in which language processing reflects an increasingly complex mental world as the comprehender draws on their knowledge of scenes and events [see also work by McRae and Matsuki (2009)showing rapid effects of world knowledge on comprehension]. Critically, Knoeferle (2019) proposes that not all effects of visual context may be caused by the same underlying mechanism-distinct language-world relations elicit distinct context effects-and demonstrates a strong role for comprehender-specific characteristics modulating context effects during comprehension.…”
Section: Language Comprehension and Visual Context: An Integrated Persupporting
confidence: 73%
“…Our findings show that verb-action relations and nonreferential emotional world-language relations seem to inform real-time language processing to different degrees (see Knoeferle, 2019 for a comprehensive review). Action effects were pervasive in all age groups; the speaker's emotional prime face only facilitated younger adults' sentence processing.…”
Section: Discussionmentioning
confidence: 91%
“…Alternatively, do they modulate comprehension in distinct ways (Knoeferle et al, 2014 ; Kreysa et al, 2018 ; Knoeferle, 2019 )—much like different sorts of linguistic knowledge are processed distinctly (Hagoort, 2003 ; Huettig and McQueen, 2007 ; Bastiaansen and Hagoort, 2015 ; Lapinskaya et al, 2016 )? Initial evidence suggests that referential and non-referential world-language relations modulate comprehension and visual attention in distinct ways with referential relations eliciting more visual attention to objects than non-referential relations (Cooper, 1974 ).…”
Section: Introductionmentioning
confidence: 99%
“…They point out that the majority of studies has examined decontextualized metaphors only, even though metaphors are typically embedded in rich communicative and extralinguistic contexts. Previous psycholinguistic research has shown that literal utterances are integrated incrementally with context, influencing even the earliest stages of sentence interpretation (see Huettig et al, 2011;Knoeferle, 2019;Knoeferle & Guerra, 2016;Tanenhaus & Trueswell, 2006, for reviews). The integration of an utterance in context determines the unfolding interpretation and helps generate expectations about upcoming input (Altmann & Kamide, 1999;Sedivy et al, 1999;Tanenhaus et al, 1995, among many others).…”
Section: Introductionmentioning
confidence: 99%